2013
DOI: 10.7314/apjcp.2013.14.4.2439
|View full text |Cite
|
Sign up to set email alerts
|

Associations of IL-10 Gene Polymorphisms with Acute Myeloid Leukemia in Hunan, China

Abstract: We investigated the possible association of interleukin-10 (IL-10) single nucleotide polymorphisms (SNPs) and susceptibility to acute myeloid leukemia (AML) in 115 patients and 137 healthy controls. Genetic analysis of IL-10 SNPs at -819 and -592 was carried out with the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) approach. The IL-10 mRNA expression of AML patients and controls with different genotype was detected by real-time quantitative polymerase chain reaction (RT-PCR). G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…Another study conducted in China indicated that rs1800872 was associated with the overall risk of non-cardiac gastric cancer (Pan et al, 2013). For AML, only 2 studies reported an association between the rs1800871 and rs1800872 gene polymorphisms and risk of AML (Yao et al, 2013;Chen et al, 2013); these studies showed that polymorphisms in rs1800871 and rs1800872 may be associated with increased risk of AML, and were correlated with IL-10 mRNA expression in AML patients. Similarly, we also found an association between rs1800871 and rs1800872 genetic variations and AML risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study conducted in China indicated that rs1800872 was associated with the overall risk of non-cardiac gastric cancer (Pan et al, 2013). For AML, only 2 studies reported an association between the rs1800871 and rs1800872 gene polymorphisms and risk of AML (Yao et al, 2013;Chen et al, 2013); these studies showed that polymorphisms in rs1800871 and rs1800872 may be associated with increased risk of AML, and were correlated with IL-10 mRNA expression in AML patients. Similarly, we also found an association between rs1800871 and rs1800872 genetic variations and AML risk.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 SNPs had a synergistic effect on the risk of AML. Two previous studies indicated that polymorphisms in rs1800871 and rs1800872 had a significant effect on AML risk (Yao et al, 2013;Chen et al, 2013), but these studies did not explore the combination effect on cancer risk. Studies including larger sample sizes are needed to confirm the role of the rs1800871 and rs1800872 genetic variations on AML risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it has been hypothesized that IL-10 may contribute to the escape of tumor cells from immune surveillance and may favor tumor growth. Multiple epidemiologic studies have provided evidence that the IL10-A1082G genotype plays an important role in renal cell carcinoma (Uwatoko et al, 2002), hepatocellular carcinoma (Tseng et al, 2006), lung cancer (De Vita et al, 2000), leukemia (Guzowski et al, 2005;de Deus et al, 2012;Yao et al, 2013), and gastroduodenal disease (Kang et al, 2009). However, there have also been several results reporting no association of this SNP with various types of cancers (Barbisan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the varied role of IL10 has been well documented to have a beneficial effect in some diseases, and has been reported to play a critical role in cancer development and metastasis (Mocellin et al, 2005). Increased circulating IL10 has been reported in patients with different types of cancer, including hepatocellular carcinoma, infectious and autoimmune cancers, and leukemia (De Vita et al, 2000;Uwatoko et al, 2002;Guzowski et al, 2005;Tseng et al, 2006;de Deus et al, 2012, Li et al, 2012, Yao et al, 2013.…”
Section: Introductionmentioning
confidence: 99%